2023
DOI: 10.1002/hbm.26218
|View full text |Cite
|
Sign up to set email alerts
|

Classify patients with Moyamoya disease according to their cognitive performance might be helpful in clinical and practical with support vector machine based on hypergraph

Abstract: Moyamoya disease (MMD) patients were now classified according to their cerebrovascular manifestations, with cognition and emotion ignored, which attenuated the therapy. The present study tried to classify them based on their cognitive and emotional performance and explored the neural basis underlying this classification using resting‐state fMRI (rs‐fMRI). Thirty‐nine MMD patients were recruited, assessed mental function and MRI scanned. We adopted hierarchical analysis of their mental performance for new subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…These findings are consistent with those of a study conducted by Sun and colleagues, which showed that 31.5% (29 out of 92) of patients experienced cognitive dysfunctions (Sun et al, 2022). These behavioral dysfunctions are intricately linked to specific neural circuits or brain networks that support complex emotional and cognitive abilities, as well as a sophisticated interplay between them (Wang et al, 2023;Lei et al, 2020).…”
Section: Introductionsupporting
confidence: 91%
“…These findings are consistent with those of a study conducted by Sun and colleagues, which showed that 31.5% (29 out of 92) of patients experienced cognitive dysfunctions (Sun et al, 2022). These behavioral dysfunctions are intricately linked to specific neural circuits or brain networks that support complex emotional and cognitive abilities, as well as a sophisticated interplay between them (Wang et al, 2023;Lei et al, 2020).…”
Section: Introductionsupporting
confidence: 91%
“…We included 12 other studies that were not case reports nor case series (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). These comprised in total 1043 MMD patients (mean age: 37 years old; mean percentage of females: 58%).…”
Section: Results Of Other Studies On Psychiatric Symptoms In Moyamoya...mentioning
confidence: 99%